Analisis Kelayakan Produk Genteng Unggulan - Kumalasari, Nila (Jurnal Teknik Industri, 2009)
In emulation in this time especially tile product, needed careful effort to improve to be remain to exist. One of the so much industry making of tile in Malang is UD BJ Mendit, at Wendit village Glorious District of Malang. Problems faced by company is emulation with other company where more society buy tiles of other place compared to unlucky tile. For that UD BJ Mendit wishful to produce tile took a fancy to market. Pursuant to studied background hence can be made by formula of is problem of how to analyze elegibility of tile production took a fancy to market. Intention of this research is to know tile product took a fancy to unlucky area market and analyse elegibility of industrial invesment of tile of UD BJ Mendit. Method the used is analysis of cluster to form segment, formed by cluster is cluster 1 and cluster 2, cluster the dominantness shown by longer distance at dendogram on that account chosen is Karang pilang tile, election of karang pilang tile because result of anova compose F count more than F tables of 5%: 4,965. Analysis elegibility of karang pilang tile is with NPV: Rp74,478,883.00 PI: 25,44% and BEP or break even point if company sell at the price of Rp2032.11/unit.